The predictive value of BOAH scale for screening obstructive sleep apnea in patients at a sleep clinic in Scotland - Gabryelska, Agata (Sleep Breath, 2020)
OBJECTIVES: The study aimed to evaluate the diagnostic value of an original questionnaire for obstructive sleep apnea (OSA), the BOAH scale, and its ability to prioritize patients at high risk for OSA for polysomnography (PSG) examination. METHODS: The analysis included 273 patients referred to the Department of Sleep Medicine of the Royal Infirmary, Edinburgh, Scotland. The BOAH scale is comprised of 5 parameters: BMI (≥ 30 kg/m(2) gives 1 point, ≥ 35 kg/m(2) 2 points), presence of witnessed apneas during sleep (1 point), patient age ≥ 50 years (1 point), and history of hypertension (1 point). Patients were divided into three study groups depending on OSA severity defined by the apnea-hypopnea index (AHI): at least mild (AHI ≥ 5), at least moderate (AHI ≥ 15), and severe (AHI ≥ 30) OSA based on polysomnography examination. RESULTS: In the group of patients with severe OSA, the best BOAH cutoff point was 4 points based upon the Youden index. With 4 points, the area under the receiver operating characteristic (ROC) curve was 0.778 (95% CI 0.721–0.834). Sensitivity and specificity were 57% and 89%, respectively, yielding a positive and negative predictive value of 75% and 78%, respectively, for diagnosis of severe OSAS in a patient sample with a pre-test probability for severe OSA at 37%. CONCLUSIONS: The BOAH scale in this group of Scottish patients performed comparably to other available questionnaires and scales while being shorter and simpler. The findings suggest that the BOAH scale should be considered as a useful instrument in OSA diagnosis and prioritization of high-risk patients for PSG examination.